Present Value Calculator

| Share
Present Value Calculator
Future Value Lump Sum (FV)
$
Number of Periods (t)  
Interest
Rate per Period (R)   %
Compounding per Period (m)
 
Cash Flow (Annuity)
Payment Amount (PMT) $
Growth per Payment (G)   %
Payments per Period (q)  
Payment at Period (T)  
Answer:

Present Value (PV) of the Growing Ordinary Annuity

$ 772,083.38

Calculator Use

This is a general comprehensive present value calculator that takes into account any future value, cash flow payments, compounding, growing annuities and perpetuities.  If you prefer specific present value calculations see our other present value calculators.

Period
commonly a period will be a year but it can be any time interval you want as long as all inputs are consistent.
Future Value (FV)
is a future value lump sum
Number of Periods (t)
number of periods or years
Perpetuity
for a perpetual annuity t approaches infinity.  Enter p, P, perpetuity or Perpetuity for t
Interest Rate (R)
is the annual nominal interest rate or "stated rate" per period in percent. r = R/100, the interest rate in decimal
Compounding (m)
is the number of times compounding occurs per period.  If a period is a year then annually=1, quarterly=4, monthly=12, daily = 365, etc.
Continuous Compounding
is when the frequency of compounding (m) is increased up to infinity. Enter c, C, continuous or Continuous for m.
Payment Amount (PMT)
The amount of the annuity payment each period
Growth Rate (G)
If this is a growing annuity, enter the growth rate per period of payments in percentage here. g = G/100
Payments per Period (Payment Frequency (q))
How often will payments be made during each period? If a period is a year then annually=1, quarterly=4, monthly=12, daily = 365, etc.
Payments at Period (Type)
Choose if payments occur at the end of each payment period (ordinary annuity, in arrears, 0) or if payments occur at the beginning of each payment period (annuity due, in advance, 1)
Present Value (PV)
the present value of any future value lump sum and future cash flows (payments)

Present Value Formula Derivation

The future value (FV) of a present value (PV) sum that accumulates interest at rate i over a single period of time is the present value plus the interest earned on that sum. The mathematical equation is

FV =  PV + PVi

or

FV =  PV(1 + i)

For each period into the future the accumulated value increases by an additional factor (1 + i). Therefore, the future value accumulated over, say 3 periods, is given by

FV =  PV(1 + i)(1 + i)(1 + i) = PV(1 + i)^3

or generally

FV =  PV(1 + i)^n     (1a)    and likewise we can solve for PV to get    PV_n =  FV/(1+i)^n     (1b)

The equations we have are (1a) the future value of a present sum and (1b) the present value of a future sum at a periodic interest rate i where n is the number of periods in the future. Commonly this equation is applied with periods as years but it is less restrictive to think in the broader terms of periods. Dropping the subscripts from (1b) we have:

Present Value of a Future Sum

PV =  FV/(1+i)^n      (1)

Present Value of an Annuity Formula Derivation

An annuity is a sum of money paid periodically, (at regular intervals). Let's assume we have a series of equal present values that we will call payments (PMT) for n periods at a constant interest rate i.  We can calculate FV of the series of payments 1 through n using formula (1) to add up the individual future values.

PV =  PMT/(1+i)^1 + PMT/(1+i)^2 + PMT/(1+i)^3 + ... + PMT/(1+i)^n     (2a)

multiply both sides of this equation by (1 + i) to get

PV(1 + i) =  PMT + PMT/(1+i)^1 + PMT/(1+i)^2 + PMT/(1+i)^3 + ... + PMT/(1+i)^(n-1)     (2b)

subtracting the equation for PV (2a) from the equation for PV(1 + i) (2b) most terms cancel and we are left with

PV(1 + i) - PV =  PMT - PMT/(1+i)^n

pulling out like terms on both sides

PV((1 + i) - 1) =  PMT[1 - 1/(1+i)^n]

cancelling 1's on the left

PVi =  PMT[1 - 1/(1+i)^n]

and finally, after dividing through by i, the present value of an ordinary annuity, payments made at the end of each period, is

PV =  (PMT/i)[1 - 1/(1+i)^n]     (2c)

For an annuity due, payments made at the beginning of each period instead of the end, therefore payments are now 1 period closer to the PV.  We need to discount each future value payment in the formula by 1 period. This could be written on (1b) as

PV_n =  FV/(1+i)^(n-1)

but factoring out the (1 + i)

PV_n =  [FV/(1+i)^n](1+i)

So, multiplying each payment in equation (2a), or the right side of equation (2c), by the factor (1 + i) will give us the equation of PV for an annuity due.  This can be written more generally as

Present Value of an Annuity

PV =  (PMT/i)[1-(1/(1+i)^n)](1+iT)      (2)

where T represents the type. (similar to Excel formulas) If payments are at the end of the period it is an ordinary annuity and we set T = 0.  If payments are at the beginning of the period it is an annuity due an we set T = 1.

Present Value of an Ordinary Annuity

if T = 0, payments are at the end of each period and we have the formula for present value of an ordinary annuity

PV = {PMT/i}[1-{1/(1+i)^n}]     (2.1)

Present Value of an Annuity Due

if T = 1, payments are at the beginning of each period and we have the formula for present value of an annuity due

PV =  {PMT/i}[1-{1/(1+i)^n}](1+i)     (2.2)

Present Value Growing Annuity Formula Derivation

In a growing annuity, each payment, after the first, is increased by a factor g such that payment 2 is PMT(1 + g), payment 3 is PMT(1 + g)(1 + g), payment 4 is PMT(1 + g)(1 + g)(1 + g), etc.  Modifying equation (2a) to include growth we get

PV =  PMT/(1+i)^1 + PMT(1+g)^1/(1+i)^2 + PMT(1+g)^2/(1+i)^3 + PMT(1+g)^3/(1+i)^4 + ... + PMT(1+g)^n-1/(1+i)^n     (3a)

Multiply PV by (1+i)/(1+g) to get

PV{(1+i)/(1+g)} = {PMT/(1+g)^1} + {PMT/(1+i)^1} + {PMT(1+g)^1}/{(1+i)^2} + {PMT(1+g)^2}/{(1+i)^3} + ... + {PMT(1+g)^{n-2}/(1+i)^{n-1}}     (3b)

subtracting equation (3a) from (3b) most terms cancel and we are left with

PV\left(\frac{1+i}{1+g}\right) - PV = \frac{PMT}{(1+g)} - \frac{PMT(1+g)^{n-1}}{(1+i)^{n}}

with some algebraic manipulation, multiplying both sides by (1 + g) we have

PV(1+i) - PV(1+g) = PMT - \frac{PMT(1+g)^{n}}{(1+i)^{n}}

pulling like terms out on both sides

PV(1+i-1-g) = PMT\left[1-\left(\frac{1+g}{1+i}\right)^n\right]

cancelling the 1's on the left then dividing through by (i-g) we finally get

Present Value of a Growing Annuity (g ≠ i)

PV =  \frac{PMT}{(i-g)}\left[1-\left(\frac{1+g}{1+i}\right)^n\right]

Similar to equation (2), to account for whether we have a growing annuity due or growing ordinary annuity we multiply by the factor (1 + iT)

PV = \frac{PMT}{(i-g)}\left[1-\left(\frac{1+g}{1+i}\right)^n\right](1+iT)     (3)

Present Value of a Growing Annuity (g = i)

If g = i you'll notice that (1 + g) terms cancel in equation (3a) and we get

PV =  PMT/(1+i) + PMT/(1+i) + PMT/(1+i) + ... + PMT/(1+i)

since we now have n instances of PMT/(1+i) we can reduce the equation. Also accounting for an annuity due or ordinary annuity, multiply by (1 + iT), and we get

PV =  \frac{PMT n}{(1 + i)}(1+iT)     (4)

Present Value of a Perpetuity (t → ∞ and n = mt → ∞)

For a perpetuity, perpetual annuity, time and the number of periods goes to infinity therefore n goes to infinity.  As n increases the 1/(1 + i)n term in formula (2) goes to 0 leaving

PV =  \frac{PMT}{i}(1+iT)     (5)

Present Value of a Growing Perpetuity (g < i) (t → ∞ and n = mt → ∞)

Likewise for a growing perpetuity, where we must have g<i, since (1 + i)n grows faster than (1 + g)n, that term goes to 0 in formula (3) and it reduces to

PV = \frac{PMT}{(i-g)}(1+iT)     (6)

Present Value of a Growing Perpetuity (g = i) (t → ∞ and n = mt → ∞)

Since n also goes to infinity (n → ∞) as t goes to infinity (t → ∞), we see that Present Value with Growing Annuity (g = i) also goes to infinity

PV =  [PMT*n/(1 + i)]*(1+iT) → ∞     (7)

Present Value Formula for Combined Future Value Sum and Cash Flow (Annuity):

We can combine equations (1) and (2) to have a present value equation that includes both a future value lump sum and an annuity. This equation is comparable to the underlying time value of money equations in Excel.

Present Value

PV =  \frac{FV}{(1+i)^n} + \frac{PMT}{i}\left[1-\frac{1}{(1+i)^n}\right](1+iT)     (8)

As in formula (2.1) if T = 0, payments at the end of each period, we have the formula for present value with an ordinary annuity

PV =  \frac{FV}{(1+i)^n} + \frac{PMT}{i}\left[1-\frac{1}{(1+i)^n}\right]     (8.1)

As in formula (2.2) if T = 1, payments at the beginning of each period, we have the formula for present value with an annuity due

PV =  \frac{FV}{(1+i)^n} + \frac{PMT}{i}\left[1-\frac{1}{(1+i)^n}\right](1+i)     (8.2)

Present Value when i = 0

In the case where i = 0 and we look back at equations (1) and (2a) to see that the combined present value formula can reduce to

PV =  FV + PMT*n(1+iT)

Present Value with Growing Annuity (g ≠ i)

rewritten from formula (3)

PV =  \frac{FV}{(1+i)^n} + \frac{PMT}{(i-g)}\left[1-\left(\frac{1+g}{1+i}\right)^n\right](1+iT)       (9)

Present Value with Growing Annuity (g = i)

rewritten from formula (4)

PV =  \frac{FV}{(1+i)^n} + \frac{PMT n}{(1 + i)}(1+iT)     (10)

Note on Compounding m, Time t, and Rate r

Formula (8) can be expanded to account for compounding (m).

PV =  \frac{FV}{(1+r/m)^{mt}} + \frac{PMT}{r/m}\left[1-\frac{1}{(1+r/m)^{mt}}\right](1+(r/m)T)     (11)

where n = mt and i = r/m.  t is the number of periods, m is the compounding intervals per period and r is rate per period t. (this is easily understood when applied with t in years, r the nominal rate per year and m the compounding intervals per year) When written in terms of i and n, i is the rate per compounding interval and n is the total compounding intervals although this can still be stated as "i is the rate per period and n is the number of periods" where period = compounding interval. "Period" can be a broad term.

Related to the calculator inputs, r = R/100 and g = G/100. If compounding (m) and payment frequencies (q) do not coincide in these calculations, r is converted to an equivalent rate to coincide with payments then n and i are recalculated in terms of payment frequency, q. The first part of the equation is the present value of the future sum and the second part is the present value of an annuity.

Present Value of a Perpetuity (t → ∞ and n = mt → ∞)

For a perpetuity, perpetual annuity, the number of periods t goes to infinity therefore n goes to infinity.  The FV term in equation (11) goes to 0 and the 1/(1 + i)n in the second term also goes to 0 leaving just formula (5)

PV =  \frac{PMT}{i}(1+iT)     (5)

Present Value of a Growing Perpetuity (g < i) (t → ∞ and n = mt → ∞)

Likewise for a growing perpetuity, where we must have g<i, since (1 + i)n grows faster than (1 + g)n, this term in formula (9) reduces to formula (6)

PV = \frac{PMT}{(i-g)}(1+iT)     (6)

Present Value of a Growing Perpetuity (g = i) (t → ∞ and n = mt → ∞)

Since n also goes to infinity (n → ∞) as t goes to infinity (t → ∞), we see that Present Value with Growing Annuity (g = i) (10) goes to infinity and we are back at equation (7)

PV =  [PMT*n/(1 + i)]*(1+iT) → ∞     (7)

Continuous Compounding (m → ∞)

We look back to formula (11) for present value where m is the compounding per period t, t is the number of periods and r is the compounded rate with i = r/m and n = mt.

PV =  \frac{FV}{(1+r/m)^{mt}} + \frac{PMT}{r/m}\left[1-\frac{1}{(1+r/m)^{mt}}\right](1+(r/m)T)     (11)

The effective rate is ieff = ( 1 + ( r / m ) )m - 1 for a rate r compounded m times per period.  It can be proven mathematically that as m → ∞, ieff (the effective rate of r with continuous compounding) reaches the upper limit equal to er - 1.

Present Value with Continuous Compounding (m → ∞)

Removing the m and changing r to the effective rate of r, er - 1, in formula (11), formulas (8) & (11) for Present Value become

PV =  \frac{FV}{(1+e^{r}-1)^{t}} + \frac{PMT}{e^{r}-1}\left[1-\frac{1}{(1+e^{r}-1)^{t}}\right](1+(e^{r}-1)T)

cancelling out 1's where possible we get the final formula for present value with continuous compounding

PV = \frac{FV}{e^{rt}} + \frac{PMT}{(e^r - 1)}\left[1-\frac{1}{e^{rt}}\right](1+(e^r - 1)T)     (12)

for an ordinary annuity

PV = \frac{FV}{e^{rt}} + \frac{PMT}{(e^r - 1)}\left[1-\frac{1}{e^{rt}}\right]     (12.1)

for an annuity due

PV = \frac{FV}{e^{rt}} + \frac{PMT}{(e^r - 1)}\left[1-\frac{1}{e^{rt}}\right]e^r     (12.2)

Present Value of a Growing Annuity (g ≠ i) and Continuous Compounding (m → ∞)

We can modify equation (3a) for continuous compounding, replacing i's with er - 1 and we get:

PV =  PMT/(1+e^{r}-1)^1 + PMT(1+g)^1/(1+e^{r}-1)^2 + PMT(1+g)^2/(1+e^{r}-1)^3 + PMT(1+g)^3/(1+e^{r}-1)^4 + ... + PMT(1+g)^n-1/(1+e^{r}-1)^n

which reduces to

PV =  \frac{PMT}{e^{1r}} + \frac{PMT(1+g)^1}{e^{2r}} + \frac{PMT(1+g)^2}{e^{3r}} + \frac{PMT(1+g)^3}{e^{4r}} + ... + \frac{PMT(1+g)^{n-1}}{e^{nr}}     (13a)

Multiplying (13a) by er/(1+g)

 \frac{PVe^{1r}}{(1+g)} =  \frac{PMT}{(1+g)} + \frac{PMT}{e^{1r}} + \frac{PMT(1+g)^1}{e^{2r}} + \frac{PMT(1+g)^2}{e^{3r}} + ... + \frac{PMT(1+g)^{n-2}}{e^{(n-1)r}}     (13b)

subtracting (13a) from (13b) most terms cancel out leaving

 \frac{PVe^{1r}}{(1+g)} - PV =  \frac{PMT}{(1+g)} - \frac{PMT(1+g)^{n-1}}{e^{nr}}

multiplying through by (1+g)

 PVe^{r} - PV(1+g) =  PMT - \frac{PMT(1+g)^{n}}{e^{nr}}

solving this equation for PV and adding on the term to account for whether we have a growing annuity due or growing ordinary annuity we multiply by the factor (1 + (er-1)T)

 PV =  \frac{PMT}{e^{r}-(1+g)}\left[1 - \frac{(1+g)^{n}}{e^{nr}} \right](1+(e^{r}-1)T)     (13)

Present Value of a Growing Annuity (g = i) and Continuous Compounding (m → ∞)

Starting with equation (4) replacing i's with er - 1 and simplifying we get:

PV =  \frac{PMT n}{e^{r}} (1+(e^r - 1)T)     (14)

Present Value of a Perpetuity (t → ∞) and Continuous Compounding (m → ∞)

As t → ∞, ert → ∞ and formula (12) becomes

PV = \frac{PMT}{(e^r - 1)} (1+(e^r - 1)T)     (15)

Present Value of a Growing Perpetuity (g < i) (t → ∞) and Continuous Compounding (m → ∞)

As t → ∞, n → ∞ and enr in formula (13) grows fastest causing this term to go to 0 and we are left with:

 PV =  \frac{PMT}{e^{r}-(1+g)}(1+(e^{r}-1)T)     (16)

Present Value of a Growing Perpetuity (g = i) (t → ∞) and Continuous Compounding (m → ∞)

From our equation for Present Value of a Growing Perpetuity (g = i) (7) replacing i with er-1 we end up with the following formula but since n → ∞ for a perpetuity this will also always go to infinity.

PV =  \frac{PMT n}{e^{r}} (1+(e^r - 1)T) ? ?     (17)
 

Cite this content, page or calculator as:

Furey, Edward "Present Value Calculator" From http://www.CalculatorSoup.com - Online Calculator Resource.